What a wave must be : [large type] a novel - Hunt, Angela Elwell, 1957- (Center Point Large Print, 2023)
"Seventeen-year-old Maddie is left reeling after the unexpected passing of her beloved father. No one has any idea why he betrayed them all so spectacularly, but that's exactly what his death feels like: a betrayal. With their world shattered, Maddie's grieving mother sends her to spend a few months with her grandparents, thinking a change of scenery will do her good. Susan and Frank, Maddie's grandparents, are heartbroken over the loss of their son, but they welcome Maddie as an addition to their long-empty nest. Maddie settles in and makes friends at her new school, but she still wrestles with why her father took his own life. Then an unexpected twist throws all their lives into fresh turmoil, testing the very fabric of their faith. ... Susan helps her granddaughter find hope, even as they both struggle with grief ..."--